2002
DOI: 10.1080/00071660120103675
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the microstructure on the shell strength of eggs laid by hens of different ages

Abstract: 1. The eggshell is a bioceramic material constructed of columnar calcite crystals preferentially oriented with their c-axis perpendicular to the shell surface. 2. The influence of microstructure (crystal size, shape and crystallographic orientation of crystal grains) on the mechanical properties of eggshells (shell strength) was investigated using eggs from hens of different ages. 3. There was a strong correlation between crystallographic texture and the strength of the eggshell in the case of eggs laid by you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
105
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(125 citation statements)
references
References 22 publications
10
105
0
1
Order By: Relevance
“…Increased egg weight with increasing hen age has been reported previously by many authors (Guesdon and Faure 2004;Roberts and Ball 2006;Tumova and Ledvinka 2009). The decrease in shell breaking strength as hens age, found in this study, has also been reported previously (Rodriguez-Navarro et al 2002;Roberts and Ball 2006). Shell deformation to breaking point is an indicator of the degree of elasticity of the eggshell.…”
Section: Discussionsupporting
confidence: 72%
“…Increased egg weight with increasing hen age has been reported previously by many authors (Guesdon and Faure 2004;Roberts and Ball 2006;Tumova and Ledvinka 2009). The decrease in shell breaking strength as hens age, found in this study, has also been reported previously (Rodriguez-Navarro et al 2002;Roberts and Ball 2006). Shell deformation to breaking point is an indicator of the degree of elasticity of the eggshell.…”
Section: Discussionsupporting
confidence: 72%
“…Smaller crystals in the eggshell are more compact and increase the strength of the eggshell. Structural differences can be associated with decreasing eggshell strength with age; however, the eggshell thickness was not influenced, which corresponds with Rodriguez-Navarro et al (2002). The authors reported a weaker correlation between eggshell strength and thickness or weight in young hens than older ones.…”
Section: Discussionmentioning
confidence: 85%
“…These imaging modalities revealed that occluded osteopontin is present on the surface of cleaved calcite along the {104} crystallographic faces. The elongated calcite crystals in the palisades region tend to be preferentially orientated with their (001) planes parallel (c-axis perpendicular) to the shell surface, which would orient the {104} plane at 44j tangential to the surface (Silyn-Roberts and Sharp 1986;Rodriguez-Navarro et al 2002). The {104} calcite face is the natural cleavage plane, and specific osteopontin binding to this growing crystal face during mineralization could modify the resistance of the shell to fracture along this plane.…”
Section: Discussionmentioning
confidence: 99%